The Function and Institutions of Education in Building Character and Quality of Human Resources in the Modern Era - Mitra Perania; Puput Nurayu Pratiwi; Agus Tinus (Lembaga Penelitian dan Pendidikan Mandala, 2026)
Education plays a crucial role in shaping the quality of human resources in the modern era. This study aims to analyze the functions of education and the role of educational institutions in developing individual character and competencies. This research employed a qualitative approach through a literature review by examining various scientific sources related to educational functions and institutions. The findings reveal that education serves as a medium for developing individual potential, character building, and facilitating social mobility. Educational institutions—formal, non-formal, and informal—play a significant role in implementing these functions systematically. Furthermore, educational institutions must adapt to technological advancements and global challenges through innovative learning approaches. Therefore, the synergy between educational functions and institutional roles is essential in producing competent, adaptive, and character-driven individuals in a rapidly changing world.